Unlocking the Potential of Decentralised Digital Identification Systems for Smart Cities - Castanho, Carla O.; Frantz, Rafael Z.; Chequin, Marcelo P.; Sawicki, Sandro; Roos-Frantz, Fabricia; Molina-Jimenez, Carlos; Crowcroft, Jon; Hobson, Timothy (Anais do Colóquio em Blockchain e Web Descentralizada (CBlockchain), 2025)
We argue that the absence of central authorities and trust decentralisation in decentralised ID systems enable them to achieve openness, transparency, scalability, privacy and reliability. These are highly desirable properties in several application domains including smart city services. Decentralised ID systems are only emerging. Several candidates exist at an experimental stage of development, awaiting deployment and evaluation in realistic applications. In this paper, we discuss Trustchain. We explain the features that have motivated us to use it in the implementation of smart city services. Also, we share our experience gained from its local deployment.